Bibliometric Analysis of Household Physics in Scopus Database: Approaches with Bibliometrix R-package and VOSviewer (Review of Literature on Home Physics Education) - Fatra Faiza Majid; Buyamin Buyamin (Jurnal Ilmiah Pendidikan Fisika, 2024)
This study conducts bibliometric research using the Bibliometrix R-package analysis and VOSviewer to analyse Scopus databases from 1921 to 2024, specifically focusing on physics and households. It aims to determine the number of writings on home physics education in scientific publications, analyse publication trends, identify prolific authors, identify frequently used keywords and subject areas, and identify the countries that make the most contributions to publication. The research study found one article and was the only one published in 1921, entitled "The Evolution of Nerve Muscle Mechanisms" written by Russell S.B. Davies M and Kutner R were the two most productive authors, "radon" became the most widely used author keyword in publications. Physics and astronomy became the topics of the most frequently appearing publications. The U.S. emerged as the largest publisher and the most collaborative among the countries involved in the publication. Moreover, Indonesia has become the fifth-largest publisher in the world. Out of all the study papers, only five addressed home physics education. To encourage researchers, lecturers, and students to publish findings and research results linked to household physics in international scientific journals, it is believed that the findings of this study will be useful to higher education and research institutes.